Microscale Ionic Diodes: An Overview. Issue 6 (9th March 2021) - Riza Putra, Budi; Tshwenya, Luthando; Buckingham, Mark A.; Chen, Jingyuan; Jeremiah Aoki, Koichi; Mathwig, Klaus; Arotiba, Omotayo A.; Thompson, Abigail K.; Li, Zhongkai; Marken, Frank
Abstract: Ionic rectifier membranes or devices generate uni‐directional ion transport to convert an alternating current (AC) ion current input into stored energy or direct current (DC) in the form of ion/salt gradients. Electrochemical experiments 80 years ago were conducted on biological membrane rectifier systems, but today a plethora of artificial ionic rectifier types has been developed and electroanalytical tools are employed to explore mechanisms and performance. This overview focuses on microscale ionic rectifiers with a comparison to nano‐ and macroscale ionic rectifiers. The potential is surveyed for applications in electrochemical analysis, desalination, energy harvesting, electrochemical synthesis, and in selective ion extraction. Abstract :